Time-varying volatility in Canadian and U.S. stock index and index futures markets: A multivariate analysis - Marie D. Racine; Lucy F. Ackert (Federal Reserve Bank of Atlanta, 1998)
We use a multivariate generalized autoregressive heteroskedasticity model (M-GARCH) to examine three stock indexes and their associated futures prices: the New York Stock Exchange Composite, Standard and Poor's 500, and Toronto 35. The North American context is significant because markets in Canada and the United States share similar structures and regulatory environments. Our model allows examination of dependence in volatility as it captures time variation in volatility and cross-market influences. Estimated time-variation in volatility is significant, and the volatilities are highly positively correlated. Yet, we find that the correlation in North American index and futures markets has declined over time.
Keywords: 330; Financial markets; Futures; Stock market